Confirmation of a hyperendemic focus of porcine cysticercosis in Northern Uganda: Prevalence and risk factor analysis - Ngwili, Nicholas; Ahimbisibwe, Salaviriuse; Korir, Max; Bole, Stephen; Kankya, C.; Kinyera, A.; Avudraga, S.V.; Okeny, R.S.; Kenny, R.O.; Ouma, Emily A.; Dohoo, I.; Thomas, Lian F. (2025)
Background: Taenia solium (T. solium), a neglected zoonotic tapeworm transmitted between humans and pigs, is a leading cause of acquired epilepsy in endemic areas where it is propagated by poor sanitation and pig husbandry practices. The World Health Organisation (WHO) NTD roadmap 2021–2030, recommended that targeted control interventions need to be initiated, and intensified in T. solium hyperendemic areas. Geospatial risk maps have identified Northern Uganda as a potential hyperendemic area. This study aimed to validate these findings and provide contextual evidence to support design and implementation of targeted interventions to control the parasite.